Ethics in primary care practice - Said, Abdul Hadi; Md Aris, Mohd Aznan (IIUM Press, 2022)
Family physicians deal with various types of patients from different ages, races and social backgrounds. A family physician needs to be well equipped with a clear understanding of ethical principles to enable them to manage any kind of ethical issues raised. This chapter aims to discuss the four pillars of medical ethics namely ‘patient autonomy’, ‘beneficence’, ‘non-maleficence’ and ‘justice’. These four pillars will be discussed from the primary care perspective. Beyond that, this chapter will also discuss the extended medical ethics which are particularly relevant to primary care such as patient’s confidentiality, child’s rights,